Effect of Principal’s Situational Leadership on Teacher’s Performance: A Literature Review - Hasan Hariri; Fina Septi Aristya; Sowiyah Sowiyah (Edumaspul: Jurnal Pendidikan, 2023)
Abstract The importance of principal’s leadership styles is interesting to learn, especially situational leadership styles at school. This article aims to examine the influence of the principal's situational leadership style on teacher’s performance at schools. This article used literature review to obtain the data through Google Scholar by entering the keywords “situational leadership” and “teacher’s performance”. Based on the results of the literature review, the researchers found that situational leadership style has a positive and significant effect on teacher’s performance. Keywords: situational leadership, teacher’s performance, literature review